2021
DOI: 10.1126/science.abk0058
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic evolution of dengue viruses over 20 years

Abstract: Variations in disease enhancement Secondary Dengue virus (DENV) infections can be dangerous if levels of antibodies from prior infection are inadequate to clear the virus. This RNA flavivirus exploits the presence of lower levels of heterotypic antibodies to infect immunoglobulin Fcγ receptor–bearing cells. Many RNA viruses also exhibit antigenic variation, which classically allows evasion of immune responses. Katzelnick et al . investigated whether antigenic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 49 publications
4
75
0
Order By: Relevance
“…However, differences in susceptibility to heterotypic immunity have also been linked to clade replacements, suggesting antigenic selection may have a role in DENV evolution [49,50]. In support of this hypothesis, we recently showed that antigenic traits of DENV have changed over time and are associated with both epidemic dynamics and genotype replacement [22]. The genetic determinants of antigenic differences identified in our study here will enable formal inferences into these evolutionary processes.…”
Section: Plos Pathogenssupporting
confidence: 76%
See 2 more Smart Citations
“…However, differences in susceptibility to heterotypic immunity have also been linked to clade replacements, suggesting antigenic selection may have a role in DENV evolution [49,50]. In support of this hypothesis, we recently showed that antigenic traits of DENV have changed over time and are associated with both epidemic dynamics and genotype replacement [22]. The genetic determinants of antigenic differences identified in our study here will enable formal inferences into these evolutionary processes.…”
Section: Plos Pathogenssupporting
confidence: 76%
“…To identify associations of antigenic signal with specific substitutions across all DENV proteins, we leveraged a dataset of paired whole genome sequences and neutralizing antibody titers that includes 348 DENV1-4 strains co-circulating in Bangkok, Thailand over two decades (1994 to 2014, S1 Fig) [22]. Viruses were placed onto a 3-dimensional antigenic map using antigenic cartography, a method which fits the Euclidean distance between virus-serum pairs on a map to the difference in titer measurements across a panel of reference sera [3].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…At time of infection, clear vector-associated risk factors-including habits of mosquito net use, larvicide use, and mosquito coil use-demonstrated no association with DENV infection status either. Though vector-driven selection has a significant role in overall transmission potential 34 , epidemic years may be more intensely driven by changes in serotype or genotype that underpin viral evasion of existing host immunity 13 . In our global predictor model, patient age and upper/middle vs. lower socioeconomic status were negatively correlated with DENV positivity, highlighting the preponderance of infections in children and those in poorer income brackets (Table S6).…”
Section: Regional Active Surveillance In the 2019 Cambodia Dengue Epi...mentioning
confidence: 99%
“…A recent study of data from Thailand revealed that as dengue virus evolves to evade host immunity, major epidemics result when a serotype strain becomes more antigenically similar to other serotypes than its own. 3 The force of the invading strain can result in a selective sweep, reducing viral diversity with a subsequent drop in cases. Chen and colleagues added spatial random effects to account for the introduction of new dengue serotypes, and population immunity was labelled annual anomaly in the model.…”
mentioning
confidence: 99%